Effect of different protein levels of fry feed on the production of quality tilapia (Oreochromis niloticus) fry - Sumi, KR; Das, M; Siddika, I (Journal of the Bangladesh Agricultural University, 2012)
A 4-week long feeding experiment was conducted to evaluate the effect of different protein levels of quality Tilapia (O. niloticus) fry production in Agro-3 Fish Hatchery and Culture Farm, Boilor, Trishal, Mymensingh. Four days old 1247 fry (length 0.8 cm and weight 0.012 g) were stocked at the density of 1560/m2 in twelve synthetic hapas. Four different treatments (T1, T2, T3 and T4) in three replications were used having different level of protein containing diets (T1,=35.95%, T2=40.43%, T3=45.61% and T4=50.85%) in the experiment. Feeds were supplied to fry at 4 h intervals during 24 h cycle upto satiation level. Sampling was done at 7 days interval throughout the experiment. The best growth was obtained at 35.95% protein level in T1 treatment. Therefore, a follow up second experiment with feeds having protein levels 30.12%, 33.42%, 36.19% and 39.01% encircling the best performed diet (35.95% protein) of the first experiment was conducted. Significantly (P<0.05) higher mean weight gain (g), SGR (%/day), PER, survival rate (%) and lower FCR value were found at 36.19% protein containing diet. Thus, from the results of the two experiments conducted in two consecutive years it can be said that the feed containing approximately 36% protein is the best for the production of quality tilapia fry. If farmers use 36% protein instead of 40% then it will be more economic because fish meal is costly. Further experiment can be carried with feed containing 36% protein from cheaper ingredients other than fish meal to reduce the feed cost. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11053 J. Bangladesh Agril. Univ. 9(2): 359364, 2011